An Evaluation of the Usefulness of Case-Based Explanation - Cunningham, Padraig; Doyle, Donal; Loughrey, John (Trinity College Dublin, Department of Computer Science, 2003)
One of the perceived benefits of Case-Based Reasoning (CBR) is the potential to use retrieved cases to explain predictions. Surprisingly, this aspect of CBR has not been much researched. There has been some early work on knowledge-intensive approaches to CBR where the cases contain explanation patterns (e.g. SWALE). However, a more knowledge-light approach where the case similarity is the basis for explanation has received little attention. To explore this, we have developed a CBR system for predicting blood-alcohol level. We compare explanations of predictions produced with this system with alternative rule-based explanations. The casebased explanations fare very well in this evaluation and score significantly better than the rule-based alternative.
Keywords: Computer Science